The Effect of Local Original Income and Economic Growth on the Human Development Index - Aswanto, Aswanto; Arif, Emkhad (Jujurnal Publisher, 2024)
The Human Development Index (HDI) is an indicator that can be used to measure development achievements in the quality of human life, seen from health, education and economic aspects. So these three aspects are important to improve in creating the welfare of the people of a region. In this research, there are at least two factors that can influence the human development index, namely, local original income (PAD) and economic growth. The aim of this research is to analyze local original income (PAD) and economic growth against the human development index (HDI) in Pekanbaru City. This research uses secondary data obtained from the Official Publication of the Central Statistics Agency (BPS) of Pekanbaru City, namely Regional Original Income (PAD), Economic Growth and Human Development Index (HDI) from 2018-2023. Based on the results in this research, the research data is then analyzed using the Eviews 13 application and then analyzed in the discussion. So it shows that local original income (PAD) and economic growth have a positive and significant influence on the human development index (HDI).